MASTER OF THE SHIP, MANAGER AND INSTRUCTOR - Florin IORDANOAIA (Management & Marketing, 2010)
The master of the ship is the person on the board who has the qualification and the necessary certificate of competency for running a maritime transport ship. He is the one who takes the ship into administration from the ship-owner, he is the only leader, the legal and direct chief of the entire crew, being invested with authority upon all the members of the crew. The master fulfils the attributes and displays his activity according to the legal laws of his flag, of the marine regulations and of the international conventions. In all the relationships which he establishes with physical or juridical people, the master represents the ship-owner, in a double condition, as an officer and as a commercial manager. In this paper, it is analysed the situation of the ship masters, the relationships which these masters have with the crew and the problems which appear during their voyage. At the end of the paper there are proposed measures to increase the quality of the training of the ship masters, to solve the situations connected with the members of the crew.